2017
DOI: 10.28998/rca.v15i1.2363
|View full text |Cite
|
Sign up to set email alerts
|

GERMINAÇÃO DE SEMENTES EM FUNÇÃO DO TRATAMENTO PRÉ-GERMINATIVO DE Chamaecrista

Abstract: <em>Chamaecrista </em>Moench pertence à família Leguminosae, subfamília Caesalpinioideae. Diante da escassez de informações sobre os mecanismos de germinação das espécies, objetivou-se com esse trabalho avaliar a eficiência de tratamentos pré-germinativos para superação de dormência de sementes de <em>Chamaecrista debilis</em>. Considerando-se as características aparentes das sementes em relação à espessura do tegumento e sua dureza, foi efetuado teste de germinação com 12 tratamentos: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…A dormência é um fenômeno próprio da semente, uma forma natural da resistência a fatores adversos do ambiente (ARAÚJO et al, 2017). Pode ser atribuída usualmente aos tegumentos impermeáveis e a imaturidade fisiológica ou a colheita recente, onde a germinação só ocorrerá quando esta for superada e as condições ambientais forem favoráveis ao crescimento das plântulas (CASTRO et al, 2017).…”
Section: Introductionunclassified
“…A dormência é um fenômeno próprio da semente, uma forma natural da resistência a fatores adversos do ambiente (ARAÚJO et al, 2017). Pode ser atribuída usualmente aos tegumentos impermeáveis e a imaturidade fisiológica ou a colheita recente, onde a germinação só ocorrerá quando esta for superada e as condições ambientais forem favoráveis ao crescimento das plântulas (CASTRO et al, 2017).…”
Section: Introductionunclassified
“…The superiority of HW over HA and control (Table 2) as well as 6.7 percentage units above that of water immersion treatment could indicate this technique as appropriate for C. rotundifolia. Lima et al (5) also verified this same response of C. rotundifolia using 80 °C water for 5 and 10 s; Araújo et al (15) found similar results for Chamaecrista debilis seeds treated with water at 100 °C for 5, 10, and 15 s.…”
Section: Discussionmentioning
confidence: 67%
“…Effects of dormancy-breaking techniques can vary with species. Although mechanical scarification was not evaluated in this study, it could increase seed susceptibility to damage, mostly in the smallest seeds, as described by Araújo et al (15) , who observed low efficiency of mechanical scarification on C. debilis.…”
Section: Discussionmentioning
confidence: 80%
“…This mechanism can occur due to an imposition made by the integument, due to the imbalance of substances that promote or inhibit germination, or because of the embryo (Araújo et al, 2017b). However, among these types of dormancy, tegumentary dormancy, also known as exogenous dormancy, is the most common in species in the Fabaceae family (Baskin;Baskin, 2014).…”
Section: Numbness In Forest Species Focusing On Tegumentary Numbnessmentioning
confidence: 99%